If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4s + -8 = 1 + s Reorder the terms: -8 + 4s = 1 + s Solving -8 + 4s = 1 + s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-1s' to each side of the equation. -8 + 4s + -1s = 1 + s + -1s Combine like terms: 4s + -1s = 3s -8 + 3s = 1 + s + -1s Combine like terms: s + -1s = 0 -8 + 3s = 1 + 0 -8 + 3s = 1 Add '8' to each side of the equation. -8 + 8 + 3s = 1 + 8 Combine like terms: -8 + 8 = 0 0 + 3s = 1 + 8 3s = 1 + 8 Combine like terms: 1 + 8 = 9 3s = 9 Divide each side by '3'. s = 3 Simplifying s = 3
| -5x-9x=-112 | | 6x+8x=84 | | -66=6+6x | | -13=7(2x-1)+5 | | 7x+8=10x+17 | | 6(w+4)=3w+6 | | 2(x-5)+7= | | 11x+6(3-x)=3 | | 2(x-7)+7= | | 12=-3600+3600 | | 4-5(x+1)=7 | | 7(v-5)=7 | | w-4=-10 | | x^2+y^2+4x-y-2=0 | | 3+5x(6-4+1)= | | 12x^3y^2-24x^2y^3+16x^2y^4=0 | | -4=-3(4+5x)-4(-2+6x) | | 4+3x=17-6x | | 5-3x=15+0.5x | | 10x-24=2x+8 | | 9-5x=5-3x | | 7x+4=2x+2 | | (9)(7)-(5)(-2)= | | 3-2n=11 | | 7-(-1-4)= | | 8+3x=18+4x | | -2-4+7+3(-4)+17= | | 4-9x=26+2x | | 2(3x+4)=42 | | 5(x-2)+4=-11 | | 6+4(-4)= | | t^3-9t=0 |